Colonialism and indian economy - "Bagchi, Amiya Kumar" (New Delhi, 2010)
Bringing together seminal essays of one of India's leading economic historians, Colonialism and Indian Economy presents a magisterial account of economic and social consequences of colonial rule. It underlines the importance of global history as an overarching framework for writing Indian history and provides a theoretical framework to locate India's economic experience. Through a comprehensive analysis of several aspects of Indian economy-gross domestic product, regional growth, relations between agriculture and economy, demographic changes, land tax and property rights, market relations, and bondage-this volume presents a definitive account of nature and scale of colonial exploitation. It also discusses the processes that led to de-industrialization, regional imbalances, and general impoverishment of the ordinary people. Amiya Kumar Bagchi highlights the role Indian surpluses played in catapulting Britain and other capitalist countries to global dominance. He also explores the mechanisms that generated and sustained this resource flow. In an incisive introduction, the author critically examines the writings on economic history of colonial India and delineates the features characterizing different phases of colonial rule. Underscoring the mirage of the emergence of civil society under colonial rule, he presents a penetrating narrative of the causes of underdevelopment.
Keywords: Colonialism